1987
DOI: 10.1159/000149983
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Citrus Tristeza Virus Isolates Indicated by dsRNA Analysis

Abstract: One major dsRNA of molecular weight (MW) 13.3 × 106 and two others (MW 1.9 × 106 and 0.8 × 106) were routinely detected by polyacrylamide gel electrophoresis in extracts from sweet orange {Citrus sinensis) or citron (Citrus medica) infected with each of 66 isolates of citrus tristeza virus (CTV). Several additional dsRNA were also commonly detected, usually as weakly stained bands in reproducible positions in gels, but some were very prominent, e.g., a dsRNA of MW 1.7 × 10 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…However, plants infected with such viruses as well as containing a genomic-length dsRNA also con tain smaller dsRN As [21], suggesting a different expression strategy to BPYV. The subgroup C closteroviruses, while being more similar than subgroup B closteroviruses to BPYV in particle length, also produce multiple dsRNA in in fected plants [22]. Thus, at present, BPYV does not fall easily into any of the proposed closterovirus subgroups.…”
Section: Introductionmentioning
confidence: 87%
“…However, plants infected with such viruses as well as containing a genomic-length dsRNA also con tain smaller dsRN As [21], suggesting a different expression strategy to BPYV. The subgroup C closteroviruses, while being more similar than subgroup B closteroviruses to BPYV in particle length, also produce multiple dsRNA in in fected plants [22]. Thus, at present, BPYV does not fall easily into any of the proposed closterovirus subgroups.…”
Section: Introductionmentioning
confidence: 87%
“…Several dsRNAs, including a 20 kbp molecule corresponding to the replicative form (RF) and a number of smaller species of dsRNAs, were consistently found following electrophoresis of RNA extracts from CTVinfected plants (Dodds & Bar-Joseph, 1983 ;Dodds et al, 1987). Two small dsRNA segments with estimated sizes of 0"8 kbp and 1.7 kbp were isolated and translated in vitro into two polypeptides of 27 kDa and 23 kDa, respectively (Dulieu & Bar-Joseph, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…As different isolates have been used in these studies, these conflicting results could indicate some level of variability between isolates of ACLSV. Differences between isolates of CTV involving the presence of specific dsRNA segments have already been demonstrated, and it was suggested that the dsRNA electrophoretic patterns could be used as markers to identify specific CTV isolates (Dodds et al, 1987).…”
Section: Introductionmentioning
confidence: 99%